Classics. Alloplasty of muscles and myoplasty in idiopathic scoliosis. Preliminary report - Adam Gruca (Chirurgia Narządów Ruchu i Ortopedia Polska)
Narządów Ruchu i Ortopedia Polska – Polish Orthopaedics. The author of the article presented an original technique of treating scoliosis with the use of steel springs. The springs were placed on the convex side of the curvature and anchored on the transverse processes, ribs and pelvis. This idea has never been presented in English and Polish, but it can be considered as the prototype of the Vertebral Body Tethering (VBT) technique.